A New Criterion for Rupture Assessment of Rubber‐Like Materials under Mode‐I Crack Loading: The Effective Stretch Criterion. Issue 8 (6th April 2016) - Ayatollahi, Majid R.; Heydari‐Meybodi, Mahdi; Dehghany, Mohammad; Berto, Filippo
Abstract : A new criterion is presented for fracture assessment of rubber‐like materials weakened by a mode I crack. The criterion is based on two main assumptions: the existence of a damage zone around the crack tip and the dominant uniaxial nature of the stress field near the crack in rubber‐like materials. Considering these key features and employing the concepts of well‐known eight‐chain model, first, a failure criterion called the "Effective Stretch Criterion" has been proposed. Then, a procedure has been elaborated to calibrate the material parameters in the criterion. The criterion, finally, has been validated by using two sets of experimental data available in the literature. Abstract : The effective stretch criterion is proposed for rupture assessment of rubber‐like materials in the presence of a crack . The criterion employs two major parameters: critical distance rc and critical effective stretch λ ce . The former is determined from finite element analysis and the latter from a uniaxial tensile test.